Risk factors and prediction of leptospiral seropositivity among dogs and dog handlers in Malaysia - Goh, Soon Heng (MDPI, 2019)
This study determined the potential risk factors that may contribute to seropositivity among dogs and dog handlers from working dog and dog shelter institutions. Data was collected from dogs (n = 266) and dog handlers (n = 161) using a standardised guided questionnaire. Serum obtained from the dogs and dog handlers was tested using the microscopic agglutination test (MAT). A logistic regression analysis was used to predict leptospiral seropositivity of dogs and dog handlers based on potential risk factors. A total of 22.2% of dogs and 21.7% of dog handlers were seropositive. The significant predictors for the dogs’ seropositivity were presence of rats (OR = 4.61 (95% CI: 1.05, 20.33), p = 0.043) and shared common area (OR = 5.12 (95% CI: 1.94, 13.46), p = 0.001) within the organisation. Significant predictor for dog handler seropositivity was contact time with the dogs of more than six hours/day (OR = 3.28 (95% CI: 1.28, 8.40), p = 0.013) after controlling for the effect of other risk factors such as small mammal contact, rat infestation at home, flooding at housing area (within three months) and urban locality. The exposure to various disease sources identified poses risk to dogs and dog handlers. Risk could be reduced with adequate application of protection at work while handling dogs and thus limiting contact with these sources and reducing exposure to infection.